PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN (Studi pada Karyawan Kontrak Bagian Anodizing PT H.P. Metals Indonesia, Ngoro - Mojokerto, Jawa Timur) - Nurcahyati, Wiwiet Eka; Rooswidjajani, Rooswidjajani; Brimantyo, Harril (Jurnal Bisnis dan Manajemen, 2016)
The research aims to determine whether there was an effect of compensation and working environment on the performance of employees of PT. H.P. Metals Indonesia, Ngoro Mojokerto. This research was conducted using quantitative methods. The population or the subject of this study is part anodizing contract employee at PT. H.P. Metals Indonesia, Ngoro Mojokerto. The sample used in this study are as many as 200 people by using simple random sampling as a sampling method. The instrument used in this study is a questionnaire form and in the form of a Likert scale of measurement, with the test by using multiple regression analysis. The results of this study can be seen: (1) there was significant effect on compensation and work environment simultaneously toward employee performance (2) there was significant effect on compensation and work environment partially toward employee performance (3) the compensation effect is more dominant than the work environment on employee performance. This showed that the company paid more attention to the issue of compensation to improve the performance of employees.